Kinetics of reactions catalyzed by enzymes in solutions of surfactants - Biasutti, Maria Alicia (2008)
The effect of surfactants, both in water-in-oil microemulsions (hydrated reverse micelles) and aqueous solutions upon enzymatic processes is reviewed, with special emphasis on the effect of the surfactant upon the kinetic parameters of the process. Differences and similarities between processes taking place in aqueous and organic solvents are highlighted, and the main models currently employed to interpret the results are briefly discussed.